Inhabiting the exotic: Paul Bowles and Morocco - Benlemlih, Bouchra (2009)
The American writer Paul Bowles lived in Morocco from 1947 until his death in 1999, apart from visits to North Africa, Europe, Ceylon, India and the United States during this period. Bowles’ expatriation and subsequent itineraries are quite well known, but this thesis explores his interest in – indeed, preoccupation with – mediations and a state of being ‘in-between’ in a selection of his texts: the translations, his autobiography and his fiction.